2013
DOI: 10.1002/ajmg.a.36189
|View full text |Cite
|
Sign up to set email alerts
|

A novel germline PIGA mutation in Ferro‐Cerebro‐Cutaneous syndrome: A neurodegenerative X‐linked epileptic encephalopathy with systemic iron‐overload

Abstract: Three related males presented with a newly recognized x-linked syndrome associated with neurodegeneration, cutaneous abnormalities, and systemic iron overload. Linkage studies demonstrated that they shared a haplotype on Xp21.3– Xp22.2 and exome sequencing was used to identify candidate variants. Of the segregating variants, only a PIGA mutation segregated with disease in the family. The c.328_330delCCT PIGA variant predicts, p.Leu 110 del (or c.1030_1032delCTT, p. Leu344del depending on the reference sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
83
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(87 citation statements)
references
References 26 publications
3
83
1
Order By: Relevance
“…The third glycosylation gene in which a variant was identified, PGAP1 (patient 12, reported elsewhere), is important in the GPI-anchor synthesis pathway. 26 Several other genes, PIGA, PIGN, and PIGT, implicated in this pathway are known to be implicated in CVI and ID as well, 29,[37][38][39][40] and recently, also PGAP1 variants were found to be associated with CVI and ID. 29,41 RERE is another gene with a functional link with a gene known to be aberrant in CVI.…”
Section: Resultsmentioning
confidence: 99%
“…The third glycosylation gene in which a variant was identified, PGAP1 (patient 12, reported elsewhere), is important in the GPI-anchor synthesis pathway. 26 Several other genes, PIGA, PIGN, and PIGT, implicated in this pathway are known to be implicated in CVI and ID as well, 29,[37][38][39][40] and recently, also PGAP1 variants were found to be associated with CVI and ID. 29,41 RERE is another gene with a functional link with a gene known to be aberrant in CVI.…”
Section: Resultsmentioning
confidence: 99%
“…More than 20 genes are known to be important in the synthesis, assembly of the GPI anchor components, cleavage of the GPI-PSS, and eventual en bloc attachment of an assembled GPI anchor to its substrate (21). Mutations in GPI anchor synthesis enzymes are associated with many human diseases; most of these diseases affect neuronal development (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). Furthermore, a lack of GPI anchored protein in cancer cells has also been reported to be due to transcriptional silencing of the genes involved in biosynthesis of the GPI anchor (36).…”
Section: Prpmentioning
confidence: 99%
“…The family described by Swoboda et al [2013] had a much longer lifespan than did the two other reported families and manifested a number of additional features not seen in those families, most prominently CNS iron deposition and ichthyosiform skin lesions. It does appear that the in-frame deletion that was identified in this family does affect glycosylphosphatidylinositol synthesis, at least in granulocytes, so it is reasonable to conclude that the PIGA mutation is likely responsible for this effect.…”
mentioning
confidence: 82%
“…The article by Swoboda et al, [2013] is more intriguing but more challenging to interpret. There are both substantial phenotypic differences and similarities when comparing this family to those described in by Haraklova et al [2013] and Johnston et al [2012].…”
mentioning
confidence: 99%